Assessment of cardiac parameters after the administration of nicorandil before primary percutaneous coronary intervention - Ilyas, Maria; Mudassar Noor; Saleha Haroon; Kulsoom Farhat; Shabana Ali; Maheen Wahid (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess cardiac troponin I and creatine kinase-myocardial band levels, electrocardiogram changes and major adverse cardiac events after treatment with nicorandil before primary percutaneous coronary intervention. Methods: The comparative, analytical study was conducted from October to November 2022 at the Pharmacology Department of Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan, in collaboration with the Rawalpindi Institute of Cardiology, Rawalpindi. The sample comprised ST-elevated myocardial infarction patients of either gender aged at least 30 years with an ejection fraction of at least 35% undergoing primary percutaneous coronary intervention. Participants were selected based on the above-mentioned inclusion and informed consent was taken before their enrolment in this research study. The sample was randomised into control group A receiving conventional acute coronary syndrome treatment, and intervention group B receiving nicorandil in addition to the conventional treatment. Cardiac troponin I and creatine kinase-myocardial band levels, electrocardiogram changes, and major adverse cardiac events noted and compared. Data was analysed using SPSS 26. Results: Of the 140 patients, 70(50%) were in each of the 2 groups. In group B, 60(85.7%) patients achieved a completely settled ST segment on electrocardiogram compared to 25(35.7%) in group A (p=0.001). There was a significant inter-group differences with respect to cardiac troponin I value 6 hours after percutaneous coronary intervention and major adverse cardiac events (p<0.05), but creatine kinase-myocardial band level was no significantly different between the groups (p=0.761). Conclusion: Prophylactic use of nicorandil in ST-elevated myocardial infarction patients decreased the incidence of reperfusion injury. Key Words: Nicorandil, Percutaneous coronary intervention, Ischaemic reperfusion injury.